Case Report: Diagnosis and successful treatment of a rare case of steroid-refractory chronic graft-vs-host disease-related serositis - Xiong, Zilin; Wang, Zerong; Chen, Xinchuan (Frontiers in Immunology, 2025)
Chronic graft-versus-host disease (cGVHD)-related serositis is rare, and primarily presents as polyserous effusions. The low incidence and differential diagnosis impose significant challenges to the prompt diagnosis and the effective treatment of the disease. Here we report the diagnosis and treatment of a 57-year-old woman who experienced recurrent steroid-refractory cGVHD-related serositis after allogeneic hematopoietic stem cell transplantation (allo-HSCT). We thus added baricitinib, a specific JAK1/2 inhibitor, into the treatment regimen for the recurrent disease. The patient’s clinical symptoms and effusions were effectively relieved. Currently, no recurrence of serositis and significant adverse events were observed. The utilization of baricitinib might emerge as a novel promising therapeutic option for the treatment of steroid-refractory GVHD following allo-HSCT.